2017
DOI: 10.1056/nejmoa1609581
|View full text |Cite
|
Sign up to set email alerts
|

Evacetrapib and Cardiovascular Outcomes in High-Risk Vascular Disease

Abstract: BACKGROUNDThe cholesteryl ester transfer protein inhibitor evacetrapib substantially raises the high-density lipoprotein (HDL) cholesterol level, reduces the low-density lipoprotein (LDL) cholesterol level, and enhances cellular cholesterol efflux capacity. We sought to determine the effect of evacetrapib on major adverse cardiovascular outcomes in patients with high-risk vascular disease. METHODSIn a multicenter, randomized, double-blind, placebo-controlled phase 3 trial, we enrolled 12,092 patients who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
357
7
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 620 publications
(417 citation statements)
references
References 40 publications
14
357
7
4
Order By: Relevance
“…Dalcetrapib had little or no effect on apoB and LDL‐C but increased HDL‐C by about 30% . Evacetrapib reduced LDL by about 30% and raised HDL‐C by about 133% and did not reduce CVD . In contrast anacetrapib which is the largest of these studies enrolling over 30 000 patients and had double the number of events as prior studies with twice the follow‐up and was powered on putative LDL‐C difference rather than HDL‐C raising showed a 8.5% relative reduction in CVD .…”
Section: Lipid Lowering Treatments and Cvd Risk Reductionmentioning
confidence: 90%
“…Dalcetrapib had little or no effect on apoB and LDL‐C but increased HDL‐C by about 30% . Evacetrapib reduced LDL by about 30% and raised HDL‐C by about 133% and did not reduce CVD . In contrast anacetrapib which is the largest of these studies enrolling over 30 000 patients and had double the number of events as prior studies with twice the follow‐up and was powered on putative LDL‐C difference rather than HDL‐C raising showed a 8.5% relative reduction in CVD .…”
Section: Lipid Lowering Treatments and Cvd Risk Reductionmentioning
confidence: 90%
“…CETP inhibitors induce a much greater HDL‐C raising effect than nicotinic acid, and early studies focusing on lipid changes in patients with low HDL‐C levels had nurtured great expectation. However, in the cardiovascular outcome trials ILLUMINATE (torcetrapib), DAL‐OUTCOMES (dalcetrapib), and ACCELERATE (evacetrapib), the trapibs performed not better, or even worse, than placebo. The last trapib trial, REVEAL (anacetrapib), showed a meager 9% relative reduction in the risk of events among patients receiving anacetrapib, and the producer decided not to submit applications for regulatory approval.…”
Section: Hdl Trialsmentioning
confidence: 92%
“…79 Despite a 30% to 40% increase in HDL-C (and no significant changes in LDL-C), there was no difference in major cardiovascular outcomes. 79 More recently, the CETP inhibitor evacetrapib 80 increased HDL-C by 130% and lowered LDL-C by 31% compared to placebo in patients at high risk of CVD, including 68% with diabetes, but did not affect major cardiovascular events. Finally, in patients with established atherosclerotic disease, 37% of whom had diabetes, addition of the CETP inhibitor anacetrapib, increased HDL-C by 104% and reduced non-HDL cholesterol by 18%.…”
Section: Cvd Outcomes With Hdl-c Increasing Drugsmentioning
confidence: 99%